First results from the JWST early release science program Q3D: Ionization cone, clumpy star formation, and shocks in a z = 3 extremely red quasar host - Vayner, Andrey; Zakamska, Nadia L.; Ishikawa, Yuzo; Sankar, Swetha; Wylezalek, Dominika; Rupke, David S. N.; Veilleux, Sylvain; Bertemes, Caroline; Barrera-Ballesteros, Jorge K.; Chen, Hsiao-Wen; Diachenko, Nadiia; Goulding, Andy D.; et al. (The astrophysical journal, 2023)
Abstract - - Massive galaxies formed most actively at redshifts - z - = 1-3 during the period known as “cosmic noon.” Here we present an emission-line study of the extremely red quasar SDSSJ165202.64+172852.3’s host galaxy at - z - = 2.94, based on observations with the Near Infrared Spectrograph integral field unit on board JWST. We use standard emission-line diagnostic ratios to map the sources of gas ionization across the host and a swarm of companion galaxies. The quasar dominates the photoionization, but we also discover shock-excited regions orthogonal to the ionization cone and the quasar-driven outflow. These shocks could be merger-induced or—more likely, given the presence of a powerful galactic-scale quasar outflow—these are signatures of wide-angle outflows that can reach parts of the galaxy that are not directly illuminated by the quasar. Finally, the kinematically narrow emission associated with the host galaxy presents as a collection of 1 kpc-scale clumps forming stars at a rate of at least 200 - M - ⊙ - yr - −1 - . The interstellar medium within these clumps shows high electron densities, reaching up to 3000 cm - −3 - , with metallicities ranging from half to a third solar with a positive metallicity gradient, and - V - -band extinctions up to 3 mag. The star formation conditions are far more extreme in these regions than in local star-forming galaxies but consistent with those of massive galaxies at cosmic noon. The JWST observations simultaneously reveal an archetypal rapidly forming massive galaxy undergoing a merger, a clumpy starburst, an episode of obscured near-Eddington quasar activity, and an extremely powerful quasar outflow.
Gesehen am 22.01.2024